Surface Functionalization of Organosilica Nanoparticles With Au Nanoparticles Inhibits Cell Proliferation and Induces Cell Death in 4T1 Mouse Mammary Tumor Cells for DNA and Mitochondrial-Synergized Damage in Radiotherapy - Mochizuki, Chihiro; Kayabe, Yukihito; Nakamura, Junna; Igase, Masaya; Mizuno, Takuya; Nakamura, Michihiro (Frontiers in Chemistry, 2022)
Radiotherapy is one of the most effective cancer treatments. Au nanoparticles (NPs) are one of the most used X-ray sensitizing materials however the effective small sub-nm size of Au NPs used for X-ray sensitizers is disadvantageous for cellular uptake. Here, we propose the surface functionalization of organosilica NPs (OS) with Au NPs (OS/Au), which combined the 100 nm size of OS and the sub-nm size of Au NPs, and synthesized effective Au materials as an X-ray sensitizer. The X-ray sensitizing potential for 4T1 mouse mammary tumor cells was revealed using a multifaceted evaluation combined with a fluorescence microscopic cell imaging assay. The number of polyethyleneimine (PEI)-modified OS (OS/PEI) and OS/Au (OS/Au/ PEI) uptake per 4T1 mouse mammary tumor cell was the same; however, 4T1 cells treated with OS/Au/PEI exhibited significant inhibition of cell proliferation and increases in cell death by X-ray irradiation at 8Gy. The non-apoptotic death of OS/Au/PEI-treated 4T1 cells was increased by DNA and mitochondrial-synergized damage increase and showed potential applications in radiotherapy.